Selective Liquid Crystal Driving Mode Achieved by Controlling the Pretilt Angle via a Nanopatterned Organic/Inorganic Hybrid Thin Film. Issue 9 (22nd February 2021) - Song, In Ho; Jeong, Hae‐Chang; Lee, Ju Hwan; Won, Jonghoon; Kim, Dong Hyun; Lee, DongWook; Oh, Jin Young; Jang, Jong In; Liu, Yang; Seo, Dae‐Shik
Abstract: Behavior of liquid crystal (LC) is a result of interaction between the geometrical shape restrictions of the adjacent surface and molecular forces among LCs or adjacent surface. For years, continuous efforts have been made to control LC orientation and anchoring with pretilt angle for modulating the electro‐optical characteristics. For now, diverse driving modes have been developed including twisted nematic, optically compensated bend, electrically controlled birefringence, and vertical alignment. However, it has the limitation that different fabrication process should be adopted in different driving mode such as materials of alignment layer and techniques for aligning the LCs. Herein, selective LC modes are achieved by controlling the LC pretilt angle using nanopatterned organic/inorganic hybrid thin films composed of polyimide (PI) and tin oxide (SnO). It is possible to control the surface wettability according to the composition ratio between PI and SnO, thereby adjusting the pretilt angle of the LCs. Fabrication of SnO combined with PI applied via embossing allows for the large‐scale replication for LC alignment and based on consumer demand, devices can be manufactured in various modes through simple configuration changes. Therefore, an inorganic compound combined with an organic one permits designing addressable LC driving modes. Abstract : Hybrid film is used as liquid‐crystal alignment layer composed of sol–gel‐driven tin oxide and polyimide. Nanopatterns are constructed via embossing process on the hybrid film. By designing chemical composition of the hybrid film, the pretilt angle of liquid crystals can be controlled. Based on chemically engineered hybrid film, liquid crystal devices can be manufactured in four different modes through simple configuration changes.